Evaluation of the implementation of the Teaching Campus program in elementary school: A phenomenological approach - Indriani, Fitri Indriani; Holisah, Holisah (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2022)
This study aims to evaluate the implementation of the teaching campus program using an evaluation model from Stufflebeam consisting of Context, Input, Process, and Product (CIPP). The research used a qualitative method with a phenomenological approach. Data were collected by interview, observation, and documentation techniques. The data validity was done by triangulation of styles and sources. Miles and Huberman's techniques were used in data analysis: data collection, data reduction, data presentation, and conclusion. The informants include principals, teachers, students, and students as implementers of the Teaching Campus program. The results show that the implementation of the teaching campus program in elementary schools has been carried out properly in the aspects of CIPP and has a positive impact on the quality of education, especially on the program targets, namely numeracy, literacy, technology, and administration. The program's success is inseparable from various supports such as competent human resources (students and supervisors), the openness of the head of the local education office, and the cooperative school. The inhibiting factors include a lack of socialization about the program in the school, so there is a misunderstanding in giving assignments to students. On the other hand, the Teaching Campus program often accounts for errors, so the reporting of activities is not smooth, and students are often late filling out the log book because they are busy with lectures. The organizers can consider the results of this study to improve the quality of the implementation of the teaching campus program to run optimally.